CAMP and cGMP Play an Essential Role in Galvanotaxis of Cell Fragments. Issue 6 (24th November 2015) - Zhu, Kan; Sun, Yaohui; Miu, Anh; Yen, Michael; Liu, Bowei; Zeng, Qunli; Mogilner, Alex; Zhao, Min
Abstract : Cell fragments devoid of the nucleus and major organelles are found in physiology and pathology, for example platelets derived from megakaryocytes, and cell fragments from white blood cells and glioma cells. Platelets exhibit active chemotaxis. Fragments from white blood cells display chemotaxis, phagocytosis, and bactericidal functions. Signaling mechanisms underlying migration of cell fragments are poorly understood. Here we used fish keratocyte fragments and demonstrated striking differences in signal transduction in migration of cell fragments and parental cells in a weak electric field. cAMP or cGMP agonists completely abolished directional migration of fragments, but had no effect on parental cells. The inhibition effects were prevented by pre‐incubating with cAMP and cGMP antagonists. Blocking cAMP and cGMP downstream signaling by inhibition of PKA and PKG also recovered fragment galvanotaxis. Both perturbations confirmed that the inhibitory effect was mediated by cAMP or cGMP signaling. Inhibition of cathode signaling with PI3K inhibitor LY294002 also prevented the effects of cAMP or cGMP agonists. Our results suggest that cAMP and cGMP are essential for galvanotaxis of cell fragments, in contrast to the signaling mechanisms in parental cells. J. Cell. Physiol. 231: 1291–1300, 2016. © 2015 Wiley Periodicals, Inc.